OXIDATION-REDUCTION MECHANISM OF IRON IN DIOCTAHEDRAL SMECTITES: II. CRYSTAL CHEMISTRY OF REDUCED GARFIELD NONTRONITE - Manceau A.; Drits V.A.; Lanson B.; Chateigner D.; Wu J.; Huo D.; Gates W.P.; Stucki J.W. (My University, 2000)
The crystallochemical structure of reduced Garfield nontronite was studied by X-ray absorption pre-edge and infrared (IR) spectroscopy, powder X-ray diffraction, polarized extended X-ray ab-sorption fine structure (P-EXAFS) spectroscopy, and texture goniometry. Untreated and highly re-duced (>99% of total Fe as Fe 2+) nontronite samples were analyzed to determine the coordination number and the crystallographic site occupation of Fe 2+ , changes in in-plane and out-of-plane layer structure and mid-range order between Fe centers, and to monitor the changes in structural and adsorbed OH/H 2 O groups in the structure of reduced nontronite. Contrary to earlier models predict-ing the formation of fivefold coordinated Fe in the structure of nontronites upon reduction, these new results revealed that Fe maintains sixfold coordination after complete reduction. In-plane P-EXAFS evidence indicates that some of the Fe atoms occupy trans-sites in the reduced state, form-ing small trioctahedral domains within the structure of reduced nontronite. Migration of Fe from cis-to trans sites during the reduction process was corroborated by simulations of X-ray diffraction patterns which revealed that about 28% of Fe 2+ cations exist in trans sites of the reduced nontronite, rather than fully cis occupied, as in oxidized nontronite. Out-of-plane P-EXAFS results indicated that the reduction of Fe suppressed basal oxygen corrugation typical of dioctahedral smectites, and resulted in a flat basal surface which is characteristic of trioctahedral layer silicates. IR spectra of reduced nontronite revealed that the dioctahedral nature of the nontronite was lost and a band near 3623 cm –1 formed, which is thought to be associated with trioctahedral [Fe 2+ ] 3 OH stretching vibra-tions. On the basis of these results, a structural model for the reduction mechanism of Fe 3+ to Fe 2+ in Garfield nontronite is proposed that satisfies all structural data currently available. The migration of reduced Fe ions from cis-octahedra to adjacent trans-octahedra is accompanied by a dehydroxylation reaction due to the protonation of OH groups initially coordinated to Fe. This structural modification results in the formation of trioctahedral Fe 2+ clusters separated by clusters of vacancies in which the oxygen ligands residing at the boundary between trioctahedral and vacancy domains are greatly coordination undersaturated. The charge of these O atoms is compensated by the incorporation of protons, and by the displacement of Fe 2+ atoms from their ideal octahedral position toward the edges of trioctahedral clusters, thus accounting for the incoherency of the Fe-Fe1 and Fe-Fe2 distances. From these results, the ideal structural formula of reduced Garfield nontronite is Na 1.30 [Si 7.22 Al 0.78 ] [Fe 2+ 3.65 Al 0.32 Mg 0.04 ]O 17.93 (OH) 5 in which the increased layer charge due to reduction of Fe 3+ to Fe 2+ is satisfied by the incorporation of protons and interlayer Na.